The Euro zone crisis. Reasons, impacts and solutions - Czekaj, Jan (Journal of Public Governance, 2013)
The world financial and economic crisis initiated in the US in the second half of the 2000s had a considerable influence on the economic condition of many parts of the world economy. The most serious consequences can be seen in the Euro zone, particularly in Southern Europe. The most important cause of the crisis is, in the opinion of many, the public finance imbalance. The author of the present paper questions this assumption. Before the crisis, the European Union and Euro zone countries were moderately indebted in comparison with other developed countries and regions of the world economy. Fiscal imbalances should therefore be treated as the effect of the financial and economic crisis. The measures undertaken so far in order to overcome the crisis of the Euro zone are not effective. It seems to be insufficient to concentrate solely on fiscal imbalances. Due to differences in the level of economic development between the Euro zone countries, a broader scope of transfers is necessary which can be achieved only through fiscal integration. Unless the Euro zone countries become more fiscally integrated, the zone will collapse.